CONTRIBUTION OF UTTAR PRADESH TOWARDS INDIAN POTATO - Pandey, N. K.; K. Rana, Rajesh; Pandit, Arun; Chandran, K P. (Potato Journal, 2013)
Uttar Pradesh is the largest potato producing state of India. Potato performance in UP has been slightly better than that of India on area, production and productivity fronts. The analysis of the data from 1949-50 to 2004-05 indicated that UP state has been an indicator for the overall potato performance in the country. The decline in annual compound growth rates (ACGRs) of potato productivity in UP from 1980 onward and negative ACGRs of potato productivity from 2000 onward has very serious policy implications for India.